Prevalence and Risk Factors of Bipolar Disorder in District Dera Ismail Khan - Aiman Zahoor; Abdus Sami; Saif Ur Rehman; Fawad Khan; Umaira Sadiq Khan; Muhammad Zeeshan (International Journal of Global Sustainable Research, 2024)
Background: Bipolar disorder (BD) is a recurring mental health condition that causes individuals to experience alternating episodes of mania and depression. This research explores the prevalence and contributing risk factors for BD among young adults in District Dera Ismail Khan, with a focus on socio-demographic factors such as age, gender, educational background, and employment status. Methods: This cross-sectional study used the Mood Disorder Questionnaire (MDQ) to screen for BD among 339 participants, aged 17–37 years. Participants were asked questions on their age, gender, educational background, and employment status. Results: Results showed that 34.8% of participants screened positive for BD, with a higher prevalence in females (35.8%) compared to males (33.1%). A higher BD prevalence was also observed among older participants and those with advanced education. Additionally, unemployed individuals showed a greater prevalence of BD (37.1%) than employed individuals (23.2%). Conclusion: The findings demonstrate a significant prevalence of BD in District Dera Ismail Khan, particularly among females, young adults, individuals with higher education, and the unemployed. Mental health interventions tailored to these groups may help improve outcomes in this region